Supercrash: how to hijack the global economy - Cunningham, Darryl (Brighton, 2014)
"Darryl Cunningham's latest graphic investigation takes us to the heart of free-world politics and the financial crisis, as he traces the roots of our age of selfishness to the right-wing thinkers of the previous century in three fascinating chapters - Ayn Rand, Supercrash, and The Age of Selfishness. Cunningham draws a fascinating portrait of the New Right and the charismatic Ayn Rand, whose soirees were attended by the young Alan Greenspan. He shows how the US Neo-Cons have hijacked the economic debate and led the way to a world dominated by apparently unstoppable market forces. Cunningham both explains the Supercrash of 2008 and shows us what led up to it. He examines the neurological basis of political thinking, and asks why it is so difficult for us to change our minds - even when faced with powerful evidence that a certain course of action is not working. He takes a fascinating look at research carried out on the psychological differences between liberals and conservatives and suggests how their traits have defined their specific political and economic policies. "